Hakikat agama dalam teori sosial dalam al-quran - Syahrullah, Rahmat makruf (Maliki Interdisciplinary Journal, 2025)
In Islam, religion is not limited to a spiritual connection between humans and God; it also functions as a framework that governs moral and social life. The Qur’an, as the cornerstone of Islamic teachings, offers thorough guidance on how religion contributes to the development of a just, ethical, and harmonious society. However, as social conditions and cultural dynamics evolve, interpretations and practices of religion often undergo significant changes. This study explores the core essence of religion as presented in the Qur’an and examines its relevance in light of contemporary social theories, including functionalism, conflict theory, and symbolic interactionism. By employing a thematic interpretation approach (tafsir maudhu’i), the research analyzes pertinent Qur’anic verses and connects them with sociological insights to better understand the role religion plays in society. The results indicate that Islam sees religion as a foundational element in structuring social order, shaping moral conduct, and promoting communal well-being. When the understanding of religion drifts from its original Qur’anic principles, it can lead to various societal problems, including conflict, intolerance, and religious extremism. Therefore, an integrated and multidisciplinary perspective is crucial to grasp the transformation of religion and to safeguard both its spiritual and social functions in an ever-changing world.